2020
DOI: 10.3390/app10062058
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Data Hiding in Encrypted Image Based on Multi-MSB Embedding Strategy

Abstract: In this paper, a reversible data hiding method in encrypted image (RDHEI) is proposed. Prior to image encryption, the embeddable pixels are selected from an original image according to prediction errors due to adjacent pixels with strong correlation. Then the embeddable pixels and the other pixels are both rearranged and encrypted to generate an encrypted image. Secret bits are directly embedded into the multiple MSBs (most significant bit) of the embeddable pixels in the encrypted image to generate a marked e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…To verify the performance, the maximum embedding capacity is compared with the various algorithms in Table 4. In these algorithms, the maximum embedding rate that can be achieved in works [14,15,18,20,[22][23][24] does not exceed 1 bpp, but it does in works [19,25,34], and the proposed scheme is between 1-2 bpp. Chen et al [19] used block encryption and achieved stable capacity by lossless compression in blocks of 2×2 size.…”
Section: Embedded Capacity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To verify the performance, the maximum embedding capacity is compared with the various algorithms in Table 4. In these algorithms, the maximum embedding rate that can be achieved in works [14,15,18,20,[22][23][24] does not exceed 1 bpp, but it does in works [19,25,34], and the proposed scheme is between 1-2 bpp. Chen et al [19] used block encryption and achieved stable capacity by lossless compression in blocks of 2×2 size.…”
Section: Embedded Capacity Analysismentioning
confidence: 99%
“…The existing RDH-EI schemes are mainly divided into two main categories: vacating room after encryption (VRAE) [14][15][16][17][18][19][20][21][22] and reserving room before encryption (RRBE) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. They are based on the order in which the hidden room is vacated and image encryption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the images are protected by encryption algorithms that convert the original image into an unknown format, such as a noise-like or texture-like format [20][21][22][23]. In this way, it is evident that sensible information is presented in an unknown format, which leads to several tentative attacks.…”
Section: Related Workmentioning
confidence: 99%
“…In [9], Wang et al proposed a RDHEI based on multi-MSB embedding strategy. Through experimentation, they demonstrated that their approach can achieve an average ER of 1.721 bpp for the BOW-2 database.…”
Section: Introductionmentioning
confidence: 99%